Computational processing of neural recordings from calcium imaging data. (April 2019) - Stringer, Carsen; Pachitariu, Marius
Highlights: There are several promising techniques for processing calcium imaging data. Comparing the accuracy of these methods is difficult, due to lack of ground truth. The methods address to varying degrees the biases inherent to the data. One of the main biases, Z-drift, is not fully addressed by any existing method. Some methods introduce new biases, which may not be apparent to the end user. Abstract : Electrophysiology has long been the workhorse of neuroscience, allowing scientists to record with millisecond precision the action potentials generated by neurons in vivo. Recently, calcium imaging of fluorescent indicators has emerged as a powerful alternative. This technique has its own strengths and weaknesses and unique data processing problems and interpretation confounds. Here we review the computational methods that convert raw calcium movies to estimates of single neuron spike times with minimal human supervision. By computationally addressing the weaknesses of calcium imaging, these methods hold the promise of significantly improving data quality. We also introduce a new metric to evaluate the output of these processing pipelines, which is based on the cluster isolation distance routinely used in electrophysiology.